Rethinking school-university partnerships : a new way forward - Chandler, Prentice T.; Barron, Lisa (Associate professor of teacher education) (Emerald Publishing Limited : Information Age Publishing Inc., 2021)
"Rethinking School University Partnerships: A New Way Forward provides educational leaders in K-12 schools and colleges of education with insight, advice, and direction into the task of creating partnerships. In current times, colleges of education and local school districts need each other like never before. School districts struggle with pipeline, recruitment, and retention issues. Colleges of education face declining enrollment and a shifting educational landscape that fundamentally changes the way that teachers are trained and what local school districts expect their teachers to be able to do. It is with these overlapping constraints and converging interests that partnerships emerge as a foundational strategy for strengthening the education of our teachers. With nearly 80 contributors from 16 states (and Jamaica) representing 39 educational institutions, the partnerships described in this book are different from the ways in which colleges of education and school districts have traditionally worked with one another. In the past, these loose relationships centered primarily on student teaching and/or field experience placements. In this arrangement, the relationship was directed towards ensuring that the local schools were amenable to hosting students from the college of education so that the student/candidate could complete the requirements to earn a teaching license. In our view, this paradigm needs to be enlarged and shifted"--